2022
DOI: 10.7150/thno.67702
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling is controlled by Rac1 activity

Abstract: Rationale: The nuclear translocation of transcriptional factor Gli is indispensable for Hedgehog (Hh) signaling activation, whose deregulation causes cancer progressions; however, the mechanisms governing Gli nuclear translocation are poorly understood. Here, we report that the Gli translocation in response to Hh requires Rac1 activation. Methods: C3H10T1/2 cell line and mouse embryonic fibroblasts were used to explore the molecular mechanisms underlying Rac1 activity in regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…6F ). However, the expression of Gli2, one of the downstream effectors of the Shh pathway [ 38 ], was comparable in the Wdr4 A-cKO and control GNPs (Fig. 6F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6F ). However, the expression of Gli2, one of the downstream effectors of the Shh pathway [ 38 ], was comparable in the Wdr4 A-cKO and control GNPs (Fig. 6F ).…”
Section: Resultsmentioning
confidence: 99%
“…Even though we did not find out any effector of the Shh/Gli pathway from our proteomic analysis using Wdr4 A-cKO GNPs, we do not exclude the possibility that Wdr4 could impact on the Shh/Gli pathway to control GNP proliferation. Indeed, it was shown that Gli1/2 nuclear translocation in response to Shh requires Rac1 activation, and Rac1 is involved in the progression of Shh-type medulloblastoma [ 38 ]. Since we found that Wdr4 can regulate Rac1 activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that PC deficiency due to STIL overexpression could inhibit the activated form of SMO and induce the activated form of GLI1 to promote tumorigenesis in bladder cancer. Of note, we observed that GLI1 overexpression mainly located in cytoplasmic in STIL overexpressed cells, suggesting that SHH signalling activation is correlated with the nuclear translocation of GLI1 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Centchroman (CC), proven to have antitumor activity, prevents β-catenin from entering the cell nucleus to regulate the transcription of migration-related genes by suppressing Rac1/PAK1/β-catenin. As a member of the GEF family, Vav2 can also regulate the activation of Rac1/PAK1 [ 105 ]. It was found that miR-331-3p inhibits Rac1/PAK1/β-catenin by targeting Vav2, thereby inhibiting EMT and the subsequent invasion and migration of tumor cells [ 106 ].…”
Section: Molecular Mechanisms Of Cell Migration Regulated By Rac1mentioning
confidence: 99%